The making and remaking of ecological space in China: the political ecology of Chongming Eco-Island - Xie, Linjun; Flynn, Andrew; Tan-Mullins, May; Cheshmehzangi, Ali (2019)
This paper contributes to debates on urban sustainable development through a critical examination of current state-led and Ecological Modernization-guided eco-developments in China. Using Chongming Eco-Island as a case study, we critically evaluate the practices and effects of current Chinese eco-development alongside ecological, economic, and social dimensions. Adopting an alternative analytical approach – political ecology, our analysis brings to the fore a host of stakeholders’ voices and knowledge (especially the often-marginalized grassroots), triangulated with archival research and on-site observation. Our findings show that the Eco-Island development with an Ecological Modernization bias generates unintended and adverse results for the local community and the environment. We argue that political ecology, as both a contesting perspective in sustainable development and as a critical analytical method in understanding society-environment relations, serves as an attractive alternative strategy for those seeking to analyze a more nature-focused, locally-relevant means to promote just planning for urban sustainability.